Mohammad Mahdi Al-Jawahiri’s Literary Stance toward Leading Figures of Modern Arabic Poetry and Prose - Abd Ali Janzil, Hadi; Abdul-Hussein Abd El Sayed, Nael ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
the poet Mohammad Mahdi Al-Jawahiri toward leading figures of modern Arabic poetry and prose, considering them a methodological entry point to uncover his aesthetic vision and intellectual and cultural project. The research seeks to analyze the nature of his critical and creative relationships with a number of Arab poets and writers, such as Ahmed Shawqi, Hafiz Ibrahim, Al-Mazni, Omar Al-Fakhouri, Elias Abu Shabaki, Bishara Al-Khouri, and Samih Al-Qasim, in addition to Ameen Rihani and Taha Hussein. The study demonstrates that Al-Jawahiri did not approach these literary figures as isolated individuals detached from their social context, but rather as cultural symbols embodying the dialectic between freedom and authority, and between creativity and commitment. It concludes that Al-Jawahiri’s stances represent an integrated cultural project that connects literature to the collective consciousness of the nation and affirms the role of the intellectual in questioning reality and formulating a critical position toward it. DOI: https://doi.org/10.54633/2333-024-057-020